Towards a Reference Architecture for ADM-based Modernization Tools - Santos, Bruno Marinho; Landi, André de Souza; de Guzmán, Ignacio García-Rodríguez; Piattini, Mario; de Camargo, Valter Vieira (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Context: The modernization of a legacy software system is a reality of companies that need to improve their systems. Architecture-Driven Modernization (ADM) is a model-driven blueprint that support modernization engineers in the modernization processes. ADM considers the usage of reengineering and model driven architecture (MDA) concepts and advocates the employment of standard metamodels, such as Knowledge Discovery Metamodel (KDM). One of the main challenges while considering ADM is on how modernization tools (MTs) should be developed in order to allow the success of modernization projects that follows the ADM blueprint. Objective: In this paper we address the main requirements and guidelines on how modernization tools should be designed by means of a Reference Architecture (RA) for ADM-based Modernization Tools named RADMoTo. Methodology: We followed a four-steps methodological process to build RADMoTo and to evaluate it we submitted the RA technical report and a survey to ADM experts and software architects in order to get a feedback of the RA acceptance level. Results: As a result, we found out that, in general, the participants believe that our RA provides an acceptable level while considering the architectural views. Conclusion: The feedback from the participants helped in the improvement process of the RA. Thus, we claim that this paper provides concrete guidelines on how modernization tools should be designed and on how architectural instances derived from our RA could benefit from reusability and interoperability.